A Phase II Trial of the Double Epigenetic Priming Regimen Including Chidamide and Decitabine for Relapsed/Refractory Acute Myeloid Leukemia - Yin, Jia; Wan, Chao-Ling; Zhang, Ling; Zhang, Hao; Bai, Lian; Zhou, Hai-Xia; Xu, Ming-Zhu; Chen, Li-Yun; Qian, Chong-Sheng; Qiu, Hui-Ying; Chen, Su-Ning; Tang, Xiao-Wen; et al. (Frontiers in Oncology, 2021)
Objective: To explore the role of chidamide, decitabine plus priming regimen in the salvage treatment of relapsed/refractory acute myeloid leukemia. Methods: A clinical trial was conducted in relapsed/refractory acute myeloid leukemia patients using chidamide, decitabine, cytarabine, idarubicin, and granulocyte-colony stimulating factor, termed CDIAG, a double epigenetic priming regimen. Results: Thirty-five patients were recruited. Three patients received 2 treatment cycles. In 32 evaluable patients and 35 treatment courses, the completed remission rate (CRR) was 42.9%. The median OS time was 11.7 months. The median OS times of responders were 18.4 months, while those of nonresponders were 7.4 months (P = 0.015). The presence of RUNX1 mutations was associated with a high CRR but a short 2-year OS (P = 0.023) and PFS (P = 0.018) due to relapse after treatment. The presence of IDH mutations had no effect on the remission rate (80.0% vs. 73.3%), but showed a better OS (2-year OS rate: 100.0% vs. 28.9%). Grade 3/4 nonhematological adverse events included pneumonia, hematosepsis, febrile neutropenia, skin and soft tissue infection and others. Conclusion: The double epigenetic priming regimen (CDIAG regimen) showed considerably good antileukemia activity in these patients. Adverse events were acceptable according to previous experience. The study was registered as a clinical trial.